2017
DOI: 10.1111/ecno.12115
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy, Debt Burden and Impulsivity: A Mediation Analysis

Abstract: After the 2008 crisis, EU regulatory authorities and policy makers started to devote resources to improve households’ financial literacy, considered as a key element of debt decisions. However, the role of another crucial determinant of debt burden has been neglected in such financial education programmes. The present study examines the role of impulsivity and financial literacy as predictors of debt burden in a sample of 445 individuals. An ad‐hoc built indicator of financial literacy and scores on the Barrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
(44 reference statements)
1
24
0
1
Order By: Relevance
“…Besides, these individuals are less capable to take corrective steps to improve their habits, despite knowing the dangers of over-indebtedness. Indeed, recent studies have highlighted that impatient individuals heavily discount the benefits of being financially literate (Gathergood, 2012;Ottaviani & Vandone, 2018) and are less likely to participate in credit counseling programmes even though those programmes are provided for free (Meier & Sprenger, 2013). Taken together, these results point to the urge for policymakers to set policy measures specifically tailored to impulsive individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, these individuals are less capable to take corrective steps to improve their habits, despite knowing the dangers of over-indebtedness. Indeed, recent studies have highlighted that impatient individuals heavily discount the benefits of being financially literate (Gathergood, 2012;Ottaviani & Vandone, 2018) and are less likely to participate in credit counseling programmes even though those programmes are provided for free (Meier & Sprenger, 2013). Taken together, these results point to the urge for policymakers to set policy measures specifically tailored to impulsive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies highlight that less financially knowledgeable individuals tend to hold higher levels of debt‐to‐income ratio and more difficulties in paying off debt (Disney & Gathergood, ; Lusardi & Tufano, ; Robb, ). Given existing evidence on impulsivity as a mediator of the impact of financial literacy on debt, even after controlling for financial wealth, we expected the association between impulsivity and over‐indebtedness to be stronger in less financially knowledgeable individuals (Ottaviani & Vandone, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent lab experiment [13] showed that an increase in financial literacy amplifies the tendency to wait for delayed higher rewards. Similarly, Meier and Sprenger [70] and Ottaviani and Vandone [71] found that impulsive / less patient individuals have lower levels of financial literacy.…”
Section: Poverty Economic Preferences and Financial Literacy: What Dmentioning
confidence: 92%
“…However, although there is some direct evidence that poor financial literacy is associated with higher levels of debt (e.g., Lusardi & Tufano, 2015, in a population sample; Norvilitis et al., 2006, among college students), such evidence is limited compared with the attention the question has been given. Some studies find no effect, a relatively weak effect, or an effect that is mediated by other factors (e.g., Gathergood, 2012; Ottaviani & Vandone, 2018; Potrich & Viera, 2018). There is a need for prospective study to investigate experimentally whether raising general financial literacy through education does reduce the risk of subsequent debt problems.…”
Section: The Psychology Of Getting Into Debtmentioning
confidence: 99%